2015
DOI: 10.1371/journal.pntd.0003828
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Transcriptome Profiling in Heart of Trypanosoma cruzi-Infected Mice: Parasitological and Cardiological Outcomes

Abstract: Chagas disease is caused by the parasite Trypanosoma cruzi, and it begins with a short acute phase characterized by high parasitemia followed by a life-long chronic phase with scarce parasitism. Cardiac involvement is the most prominent manifestation, as 30% of infected subjects will develop abnormal ventricular repolarization with myocarditis, fibrosis and cardiomyocyte hypertrophy by undefined mechanisms. Nevertheless, follow-up studies in chagasic patients, as well as studies with murine models, suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(109 citation statements)
references
References 35 publications
9
94
1
1
Order By: Relevance
“…The modulation of miRNAs from the hearts of T. cruzi-infected mice is positively correlated with a parasitemia peak at 30 days post-infection (dpi), as observed for miR-146b, miR-21, miR-142-3p, and miR-142-5p, while a negative correlation is observed for miR-145-5p and miR-149-5p and also suggests the regulation of genes involved in the pathophysiological conditions of experimental infection, such as calcium and potassium channels and electrocardiography (ECG) parameters [116], as shown in Figure 3. The dysregulation of miR-133 and miR-208 have been correlated with heart genes that are related to cardiovascular disease in chronic Chagas patients and acute T. cruzi-infected mice [112,114,115].…”
Section: Trypanosoma-host Interactionsmentioning
confidence: 90%
“…The modulation of miRNAs from the hearts of T. cruzi-infected mice is positively correlated with a parasitemia peak at 30 days post-infection (dpi), as observed for miR-146b, miR-21, miR-142-3p, and miR-142-5p, while a negative correlation is observed for miR-145-5p and miR-149-5p and also suggests the regulation of genes involved in the pathophysiological conditions of experimental infection, such as calcium and potassium channels and electrocardiography (ECG) parameters [116], as shown in Figure 3. The dysregulation of miR-133 and miR-208 have been correlated with heart genes that are related to cardiovascular disease in chronic Chagas patients and acute T. cruzi-infected mice [112,114,115].…”
Section: Trypanosoma-host Interactionsmentioning
confidence: 90%
“…For example, miR-155 increases the production of inflammatory cytokines and activates immune effector cells in the heart during infection, but switches to an anti-inflammatory and cardioprotective role during sepsis (110). Similarly, miR-21 levels correlate positively with the severity of myocarditis (111,112), although one study showed opposing result that injecting miR-21 to mice with VMC relieves disease severity (113).…”
Section: Biogenesis and Functions Of Mirnasmentioning
confidence: 99%
“…In mice with EAM, miR-223-3p ameliorated inflammatory response by targeting pyrin domain-containing-3 (NLRP3) inflammasome which is a multiprotein complex and sensor in innate immune cells (140). miR-21, miR-146b, and miR-155 are consistently up-regulated in patients with acute VMC (141), and mice with myocarditis induced by CVB3 or T. cruzi (112). Consistent with this, intravenous injection of miR-21 and -146b antagonists decreased the expression levels of Th17 and RORγt, and attenuated cardiac inflammation and myocardial damage in a murine model of VMC (111).…”
Section: Immune Status-related Mirnasmentioning
confidence: 99%
“…After histopathologic examinations, total miR samples were extracted from the parenchyma of the SC. This is followed by the quantitative RT-PCR [27][28][29][30][31][32][33].…”
Section: Isolation Of Mir Samples and The Rt-pcrmentioning
confidence: 99%